Integration of Local Wisdom Character Values and Creative Processes through Jumputan Batik Making in Fine Arts Learning at Elementary Schools - Indri Apriyani; Sriyanto Sriyanto; Anang Widhi Nirwansyah; Ana Andriani; Indri Apriyani; Sriyanto Sriyanto; Anang Widhi Nirwansyah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Art learning in elementary schools is important in fostering creativity and character, but it still tends to be oriented towards the end result and has not integrated the creative process and local wisdom values. The purpose of this study was to analyze the integration of local wisdom character values and the creative process in making jumputan batik in art learning in elementary schools. The research method was qualitative with a case study design in 5 elementary schools in the Cilacap area. The research subjects consisted of 5 teachers and 15 sixth-grade students. Data were collected through interviews, observations, and document analysis. Data were analyzed using an interactive model through data condensation, presentation, and drawing conclusions. Data were validated by triangulation of techniques and sources. The results of the study indicate that the integration of local wisdom values and the creative process through jumputan batik making in elementary schools takes place contextually and diversely. The local wisdom-based character values that emerged include creativity that develops from various sources of ideas; precision in the binding and coloring process; cooperation through the division of tasks in groups; responsibility in completing tasks independently; and discipline in following each stage of the activity. The students' creative process also progresses in stages, from exploring ideas, using guided and independent techniques, and selecting colors influenced by discussions and cultural meanings. It was concluded that the process of making jumputan batik fosters students’ creativity while simultaneously instilling local wisdom-based character values through meaningful and contextual creative experiences. Collaboration from all parties is essential in art project-based learning to optimally develop students' character values and creativity.